Research Trend of Dynamic Fluid in Learning: A Bibliometric Analysis - Misbah, Misbah; Hamidah, Ida; Sriyati, Siti; Samsudin, Achmad (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This article provides an extensive bibliometric literature review on dynamic fluid in learning. This study aims to analyze research trends related to dynamic fluid in learning topics in 2019-2023 through bibliometric analysis with the Scopus database. Based on the criteria obtained, 327 articles were obtained from 1598 documents. The articles have already been analyzed from the journal and conference proceedings indexed in Scopus. Dynamic fluid research trends in learning are also reviewed based on the number of articles published each year, sources of publication (both journals and proceedings), the most productive countries, the most productive authors based on the number of documents, and co-occurrences using VOSviewer. The results show that the dynamics of learning are increasing every year. JPCS has published the most dynamic fluid articles in learning. The United States, as the most productive country, researches this topic. In addition, most of the prolific authors come from the US. A visualization of dynamic fluid research trends in learning using VOSviewer software obtained five clusters. The results of this study provide direction for further research on fluid dynamics in learning.